1996
DOI: 10.1164/ajrccm.153.6.8665059
|View full text |Cite
|
Sign up to set email alerts
|

Color Doppler ultrasound signals of thoracic lesions. Correlation with resected histologic specimens.

Abstract: Sixty-eight patients with thoracic lesions (48 with lung cancer and 20 with benign lesions) underwent color Doppler ultrasound (US) examinations. Of those, 21 patients (13 with lung cancer and eight with benign lesions) also received resections, and the correlation between color Doppler US signals and resected histologic specimens was evaluated. Our results showed that three patterns of color Doppler US signals could be detected and confirmed: pulsatile flow (artery), constant flow, and triphasic flow (pulmona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
52
0

Year Published

1997
1997
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(52 citation statements)
references
References 0 publications
0
52
0
Order By: Relevance
“…The depth of these lesions is accurately measured using US; however, sonagraphic rib shadowing can prevent the accurate determination of their size in the longitudinal axis (Figure 7). Color Doppler may aid in distinguishing benign from malignant masses, with around two-thirds of malignant masses demonstrating a color Doppler signal (low-impedance flow) because of increased vascularity (34,35). A pulsatile or triphasic flow pattern is often observed in either benign or malignant mass lesions, whereas a constant flow pattern correlates better with malignancy (37).…”
Section: Lung Tumorsmentioning
confidence: 99%
“…The depth of these lesions is accurately measured using US; however, sonagraphic rib shadowing can prevent the accurate determination of their size in the longitudinal axis (Figure 7). Color Doppler may aid in distinguishing benign from malignant masses, with around two-thirds of malignant masses demonstrating a color Doppler signal (low-impedance flow) because of increased vascularity (34,35). A pulsatile or triphasic flow pattern is often observed in either benign or malignant mass lesions, whereas a constant flow pattern correlates better with malignancy (37).…”
Section: Lung Tumorsmentioning
confidence: 99%
“…The depth of these lesions is accurately measured using US; however, sonagraphic rib shadowing can prevent the accurate determination of their size in the longitudinal axis (Figure 7). Color Doppler may aid in distinguishing benign from malignant masses, with around two-thirds of malignant masses demonstrating a color Doppler signal (low-impedance flow) because of increased vascularity (34,35). A pulsatile or triphasic flow pattern is often observed in either benign or malignant mass lesions, whereas a constant flow pattern correlates better with malignancy (37).…”
Section: Lung Tumorsmentioning
confidence: 99%
“…Colour Doppler US may distinguish malignant from benign pulmonary masses [36,37,38]. Approximately 65% of peripheral malignant masses will demonstrate a colour Doppler signal (low-impedance flow) due to increased vascularity.…”
Section: Diagnostic Transthoracic Ultrasonographymentioning
confidence: 99%
“…Approximately 65% of peripheral malignant masses will demonstrate a colour Doppler signal (low-impedance flow) due to increased vascularity. A constant flow pattern correlates with malignancy, whereas a pulsatile or triphasic flow pattern is often observed in either benign or malignant mass lesions [36]. At least one study found that residual peripheral metastases demonstrated a reduced colour Doppler signal following chemotherapy [39].…”
Section: Diagnostic Transthoracic Ultrasonographymentioning
confidence: 99%